The Effect of Slip Polymer Additives on the Characteristics of Polyethylene Films - Putri Intan Puspa Ningrum; Ani Mulyasuryani; Rakhma Febriani (Universitas Islam Indonesia, 2023)
Polymer additive’s function is to improve film quality, including slip additives which function as film surface lubricants. Slip additives affect the physical characteristics of the film as indicated by the coefficient of friction and optical properties. In this research, the influence of slip additives and the aging time of the coefficient of friction (COF) and the optical properties of polyethylene (PE) films have been studied. The optical properties of the film are measured based on the haze value and the gloss value. The additives used in this study were erucamide, stearyl erucamide, and a mixture of the two. Observations were made for 14 days at 23 °C and 50 °C. Measurements of the COF, haze value, and gloss value were carried out on days 0, 1, 3, 7, 10, and 14. The results showed that the lowest COF was produced on films with erucamide additives. Films with erucamide additives had the best friction coefficient value of 0.129 on the 3rd day of aging at 50 °C, a haze value of 4.63% and a gloss value of 56.5 GU.